La Transfiguration, un tableau protestant ? Athanase Coquerel regarde Raphaël - Hélène Guicharnaud (Chrétiens et Sociétés, 2011)
The Transfiguration is a Raphaël's controversial picture in the XIXth century. It was admired lot before; it is considered as a masterwork by Athanase Coquerel, who sees in it a free comment of the Bible. Only the face of the Christ is criticized, because we cannot represent God.